2017
DOI: 10.3847/1538-4357/aa8995
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Field-parallel Electron Acceleration in Solar Flares

Abstract: It is proposed that the coincidence of higher brightness and upward electric current observed by Janvier et al. during a flare indicates electron acceleration by field-parallel potential drops sustained by extremely strong fieldaligned currents of the order of 10 4 A m −2 . A consequence of this is the concentration of the currents in sheets with widths of the order of 1 m. The high current density suggests that the field-parallel potential drops are maintained by current-driven anomalous resistivity. The orig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
(22 reference statements)
1
5
0
Order By: Relevance
“…Interestingly, Doschek et al (2015) used the Hinode/EIS data and found that at certain footpoints of post-flare loops, a so-called inverse FIP effect developed over roughly a half an hour, where the Ar/Ca ratio was greatly enhanced relative to both coronal and photospheric ratios. Although they did not consider electric currents, the creation of such anomaly might naturally be created by forming a low-FIP ion "hole" due to depletion of the low-FIP Ca ions from the footpoint; the reported time scale is perfectly consistent with our estimate; see Equation ( 10 Haerendel (2017a) suggested that these observations show that accelerated electrons precipitated and deposited energy preferentially in the upward current ribbon. The author interpreted this observational result as an evidence for the existence of field-parallel acceleration during solar flares.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Interestingly, Doschek et al (2015) used the Hinode/EIS data and found that at certain footpoints of post-flare loops, a so-called inverse FIP effect developed over roughly a half an hour, where the Ar/Ca ratio was greatly enhanced relative to both coronal and photospheric ratios. Although they did not consider electric currents, the creation of such anomaly might naturally be created by forming a low-FIP ion "hole" due to depletion of the low-FIP Ca ions from the footpoint; the reported time scale is perfectly consistent with our estimate; see Equation ( 10 Haerendel (2017a) suggested that these observations show that accelerated electrons precipitated and deposited energy preferentially in the upward current ribbon. The author interpreted this observational result as an evidence for the existence of field-parallel acceleration during solar flares.…”
Section: Discussionsupporting
confidence: 83%
“…set et al 2015). Haerendel (2017a) suggested that these observations show that accelerated electrons precipitated and deposited energy preferentially in the upward current ribbon. The author interpreted this observational result as an evidence for the existence of field-parallel acceleration during solar flares.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Rather, we present complementary aspects of the data, emphasizing the composition and energy range of the energetic particles. We argue, based in part on the conclusion that it was unlikely that there was a well-positioned shock associated with this event, (see Rouillard et al (2019), this issue), that the event may be a good candidate for being produced by current-driven processes [as also suggested for downward accelerated electrons by Cairns et al (2003), andHaerendel (2017)], possibly associated with the reconnection that must take place during and after the release of a CME, or simply driven by the relaxation of the region to a less stressed configuration of the corona after the release of the stressed fields and large mass carried away by the CME [e.g., Chen (2011)]. In Figure 1 we present an overview of the event, with measurements by the aforementioned instruments both for context, and to provide clues to the energetic particle acceleration process.…”
mentioning
confidence: 85%
“…It has since been confirmed that the number density of the precipitating electrons in HXBs is comparable with the ambient electron number density [15]. More recent observations [16] suggest that the precipitating electrons are confined to very narrow current channels where they are accelerated by a parallel electric field [17,18]. A flare model needs to include this bulk energization as the main form of dissipation for the released magnetic energy.…”
Section: Introductionmentioning
confidence: 99%